Dynamic response of tension leg platform with tuned mass dampers (Journal of Naval Architecture and Marine Engineering, 2013)
Tension Leg Platform (TLP) is a taut-moored compliant offshore platform that deploys tethers under high initial pretension to counteract the excess buoyancy. TLPs show large amplitude responses under the encountered lateral forces, which challenges the serviceability of the platform in critical sea states. One of the passive control device i.e. Tuned Mass Damper (TMD) is attempted in the present study to control large amplitude motion of TLPs. In the present study, response control of TLP using single and multiple TMDs is compared. Optimized parameters of multiple tuned mass dampers (MTMD) are obtained using H2 optimization algorithm for the maximum control of the motion of the platform. Based on the studies conducted, it is seen that MTMD systems show better response control in comparison to the single TMD. Higher robustness of the MTMD system is also examined to highlight the use of MTMD over a wide range of excitation frequencies in extreme sea states.DOI: http://dx.doi.org/10.3329/jname.v10i2.16184